Propagación de plantulas de pinus radiata (D. Don en camas elevadas y diferentes frecuencias de fertilización) - Viera Sinchiguano, Edgar Stalín (2013)
The research was conducted on the property of Mr. Stalin Viera , located in Cotopaxi Provine in , Saquisilí County, in Manizales neighborhood. Whose geographical location is 78 ° 37 " 19 ' Lat East and 00 ° 59" 47 ' North Longitude , with an altitude of 2900 meters above sea level. The trial had a 112 day duration and the main objective is the spread of radiata pine seedlings on raised beds and different frequence of fertilization. Raised bed ( 40 cm ) , T2 : : phosphorus fertilization (1.2 kg Super phosphate substrate triple/m3 ) , T3 : Increase fertiirigation frequency (3 times per week), T4 : Increased frequency was evaluated 4 treatments T1 soil fertilization (3 times / production cycle) and a witness. A design Randomized Complete Block (RCBD) with five treatments and four replications was used. To determine the statistical differences between average test Tukey multiple range (≤ 00.5) was used. Experimental plots consisted of 1 plastic tray of 40 plants and the net plot has 18 plants per tray. The evaluation was done measuring the umber of plants that germinated from day 12 to 28 after sowing. Also measured the seedling height and diameter at 4,8,12,15 weeks after germination. The evaluation also measure length of seedling production cycle until they are 20 cm in height and 3mm DAC and economic analysis of treatments. The treatments T2 (phosphate fertilizer) had the best performance in the germination of the seedlings, accounting for 91 % of plants germinated in from day 20 to 25. The best treatment in plant height and diameter corresponded to T4 (frequency increase soil fertilization) it presented average height of 28.3 cm and 3.7 mm in diameter The production cycle was lower for T4 (Increased frequency of soil fertilization) 84 days and the major cycle corresponded to T1 (raised bed) with 120 days. The economic analysis determined that T4 (soil fertilization rate increase) presented the best rate Benefit / Cost (B / C) with 1.6 meaning that for every dollar spent gets one dollar and 60 cents